1986
DOI: 10.1111/j.1540-8159.1986.tb06633.x
|View full text |Cite
|
Sign up to set email alerts
|

QT Prolongation and Torsade de Pointes Ventricular Tachycardia Produced by Ketanserin

Abstract: A 65-year-old man with arterial hypertension received oral treatment with Ketanserin, a new drug, during a period of five months. He developed marked QT interval prolongation and have several Stokes-Adams attacks. A Holter recording obtained during one of these episodes showed torsade de pointes ventricular tachycardia. The arrhythmias occurred during maximum QT interval prolongation. The correlation between Ketanserin and QT interval prolongation was evaluated by using several Holter studies during administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Moreover, ketanserin was also applied for pharmacological management of complex regional pain syndrome ( Luca‐Vinhas et al ., 2006 ; Rowbotham, 2006 ). However, ketanserin was found to have the cardiac toxicity that prolongs cardiac QTc interval in the ECG ( Aldariz et al ., 1986 ; Zehender et al ., 1989 ; Frishman and Grewall, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ketanserin was also applied for pharmacological management of complex regional pain syndrome ( Luca‐Vinhas et al ., 2006 ; Rowbotham, 2006 ). However, ketanserin was found to have the cardiac toxicity that prolongs cardiac QTc interval in the ECG ( Aldariz et al ., 1986 ; Zehender et al ., 1989 ; Frishman and Grewall, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated the existence of both I Kr and I Ks in human ventricular myocytes ( Li et al ., 1996 ). The prolonged QTc interval of the ECG observed in clinical patients ( Aldariz et al ., 1986 ; Zehender et al ., 1989 ; Frishman and Grewall, 2000 ) is likely to be related to the block of cardiac I Kr and/or I Ks . We found, however, that ketanserin blocked hERG channels, but not I Ks channels.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, prolongation of the QT interval has been reported in KT-treated patients. [5][6][7] The antiarrhythmic action of KT in ischemic/reperfused rat heart has been ascribed to a prolongation of APD. 8 Recently, we reported that KT prolongs APD by exerting an open channel block of the fast component of the delayed rectifier potassium current (IKr) in guinea pig ventricular myocytes, with little or no effect on the inward rectifier potassium current (IK1) .9 It has been shown that transient potassium outward current (Ito) is the major outward repolarizing current in ferred to a 500-,uL chamber mounted on the stage of an inverted microscope (Nikon Inc).…”
Section: Ketanserin Inhibits Depolarization-activatedmentioning
confidence: 99%
“…Furthermore, side effects are more abundant after intravenous administration (usually lOmg) which initially leads Table VII. In several placebo-controlled studies ketanserin has caused a slight and dose-dependent prolongation of the QT interval (Aldariz et al 1986;Cameron et al 1987;Stott et al 1986), which has clinical implications with respect to the development of ventricular arrhythmias. to higher Cmax values than those reported for the common oral dosages (Jennings & Opie 1987;Milei et al 1987;).…”
Section: Relationship Between Plasma Concentration and Adverse Effectsmentioning
confidence: 99%